Inciting Genocide with Words - Wilson, Richard Ashby (2015)
During the 1994 genocide in Rwanda, observers emphasized the role of media propaganda in inciting Rwandan Hutus to attack the Tutsi minority group, with one claiming that the primary tools of genocide were “the radio and the machete.” As a steady stream of commentators referred to “radio genocide” and “death by radio” and “the soundtrack to genocide,” a widespread consensus emerged that key responsibility for the genocide lay with the Rwandan media. Mathias Ruzindana, prosecution expert witness at the ICTR, supports this notion, writing, “In the case of the 1994 genocide in Rwanda, the effect of language was lethal . . . hate media . . . played a key role in the instigation of genocide.” Legal precedents from the International Criminal Tribunal for Rwanda (ICTR) solidified this view as doctrine, finding that certain public statements by Hutu political leaders and RTLM radio broadcasts constituted direct and public incitement to commit genocide against ethnic Tutsis